2014
DOI: 10.1016/j.scitotenv.2014.07.054
|View full text |Cite
|
Sign up to set email alerts
|

How do microlocal environmental variations affect microbial activities of a Pinus halepensis litter in a Mediterranean coastal area?

Abstract: Mediterranean coastal ecosystems suffer many different types of natural and anthropogenic environmental pressure. Microbial communities, major conductors of organic matter decomposition are also subject to these environmental constraints. In this study, our aim was to understand how microbial activities vary at a small spatio-temporal scale in a Mediterranean coastal environment. Microbial activities were monitored in a Pinus halepensis litter collected from two areas, one close to (10 m) and one far from (300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…2. Laboratories should collaborate to examine the reliability (and validity) of different coding schemes, preferable on openly available data sets (Kleinberg, Nahari, Arntz, & Verschuere, 2017;Kleinberg, van der Toolen, Vrij, Arntz, & Verschuere, 2018;Mihalcea, Narvaez, & Burzo, 2014;Ott, Choi, Cardie, & Hancock, 2011;Ott et al, 2013; P erez-Rosas, Abouelenien, Mihalcea, & Burzo, 2015). 3.…”
Section: Commentary #4 By Masip: the Need To Complement Cbca (And Rm)mentioning
confidence: 99%
“…2. Laboratories should collaborate to examine the reliability (and validity) of different coding schemes, preferable on openly available data sets (Kleinberg, Nahari, Arntz, & Verschuere, 2017;Kleinberg, van der Toolen, Vrij, Arntz, & Verschuere, 2018;Mihalcea, Narvaez, & Burzo, 2014;Ott, Choi, Cardie, & Hancock, 2011;Ott et al, 2013; P erez-Rosas, Abouelenien, Mihalcea, & Burzo, 2015). 3.…”
Section: Commentary #4 By Masip: the Need To Complement Cbca (And Rm)mentioning
confidence: 99%
“…This result reveals that the environmental conditions specific to the Mediterranean coastal area have a stronger effect than agriculture practices on soil functional diversity. This is consistent with previous research that has shown the significant contribution of micro‐local environmental conditions, such as exposure to salinity in coastal environments, to strong functional diversity (Qasemian et al ., ). Similarly, the selective adaptation of microbial populations to drought and osmotic stresses was responsible for the large functional diversity of microbes in a Greek Mediterranean grassland (Papatheodorou et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…above roughly 30% humidity. In previous studies, Qasemian et al (2012Qasemian et al ( , 2014 investigated litter microbial functioning in coastal habitats and showed that conductivity monitored in the field in Mediterranean coastal zones can be as high as 1500 mS cm À1 in summer. These studies revealed that, even at microlocal scales (from 10 to 300 m from shore), distance from the sea structures functional diversity, and that coastal constraints may limit microbial functioning by decreasing extracellular activities.…”
Section: Discussionmentioning
confidence: 99%
“…Qasemian et al (2014) showed that sea spray exposure can alter microbial activities: the influence of more intense salt exposure in litters close to the sea (and especially during summer drought) stresses microbial communities, leading to lower enzyme activities. However, salts can also directly impact enzymes by modifying their tridimensional conformation, interacting with their active site (which leads to inhibition of catalysis, Farnet et al, 2008) and limiting the quantity of water available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation